Trait based niche differentiation in tetrakas (Bernieridae) endemic to Madagascar: A multi-isotope approach - Yohannes, Elizabeth; Berthoud, Jean-Louis; Woog, Friederike (Frontiers in Ecology and Evolution, 2023)
Introduction Tropical rainforest species interact with each other and their environment over a wide range of spatiotemporal scales. However, our understanding of resource partitioning and the mechanisms of avian species coexistence is largely restricted to subjective visual observations or acoustic monitoring. Therefore, the relative magnitudes of interspecific and intraspecific differences in resource use have remained difficult to quantify, particularly regarding different diets and habitat use. The eastern rainforest belt of Madagascar is inhabited by several species of insectivorous tetrakas belonging to an endemic bird family of Madagascar (Bernieridae). These species occupy similar habitats in the forest understory and are morphologically similar but because of likely differences (e.g., in foraging behaviors) we expect their foraging niches to be segregated allowing coexistence. Methods We examined the niche differentiation of four of these species: the Grey-crowned Tetraka (Xanthomixis cinereiceps), Long-billed Tetraka (Bernieria madagascariensis), Spectacled Tetraka (Xanthomixis zosterops), and White-throated Oxylabes (Oxylabes madagascariensis) in the Maromizaha rainforest in eastern Madagascar combining morphometry with stable carbon, nitrogen, and sulfur isotope ratios (δ13C, δ15N, and δ34S) from feathers. Results We show considerable variation in isotopic niche positions, niche breadth and interspecific niche overlap. In two species, the Long-billed Tetraka and Spectacled Tetraka, we found an indication of sex-specific niche space, with males exhibiting a larger isotopic niche-area relative to females. Morphological traits of five species (including the Wedge-tailed Tetraka, Hartertula flavoviridis) coupled with stable isotope data provided explanations of patterns of niche overlap and isotopic position. Discussion The observed isotopic niche differences may be explained by differences in resource acquisition strategies that might be associated with specific morphological traits and spatial distribution. This may play an important role in niche differentiation among coexisting and phylogenetically closely related species.